The use of innovative teaching strategies: a paradigm shift in english language teacher preparation (2023)
This paper highlights the importance of innovative strategies in English language classrooms. The paper also identifies areas of teaching deficiencies of teachers. Furthermore, the paper describes classroom and professional tools that will best equip English language teachers and explains, from the available literature, how PD can facilitate the effective use of ITS in English language and literature classrooms. Given the emerging trend in the classroom practices, the writers believe that teachers in today's modern classrooms need more training and professional support to improve their pedagogical knowledge and capacity. It was recommended, among others, that teachers should avail themselves of the opportunity for professional development by attending workshops and conferences, especially those that focus on the use of innovative strategies.